Testing on three determining methods of genetic diversity on earthworm species belonging to the Pheretima species group in the Mekong delta - Tung, Nguyen Thanh; Dung, Tran Nhan; Tu, Pham Minh (Academia Journal of Biology, 2012)
This paper introduced the testing results of three methods (analysis of morphological characteristics using numerical phenetics, the whole-cell proteins using SDS-PAGE and the DNA barcode sequences) used for determination of the genetic diversity of some earthworm species belonging to the Pheretima species group in the Mekong Delta (Amynthas paraalexandri, A. juliani, Metaphire posthuma, M. bahli, M. peguana, M. houlleti, Metaphire sp.8, Polypheretima elongata and P. taprobanae). All three methods yielded compatible and reliable results which appropriately explained the genetic relationships between closely related species and those between taxa of high taxonomic levels (families, genera). Phylogenetic tree constructed on the basis of DNA barcode analysis was able to indicate clearly genetic divergence between Pheretima species belonging to acoecata and coecata. Metaphire sp.8 was demonstrated to be a closely related species with M. houlleti.